Penggunaan Metode Scramble untuk Meningkatkan Hafalan Kosakata Bahasa Arab Siswa Kelas VIII - Pawindu, Jumma Wati; Syamsuddin, Naidin; Takwim, Mardi; Dzulfadli (Pedagogical Education and Review of Linguistics, 2025)
This study aims (1) to determine the application of scramble method in Arabic language learning to improve vocabulary mastery in class VIII students of SMPIT Ibnu Sina Palopo. (2) To determine the improvement of vocabulary mastery in Arabic language learning by using scramble method in class VIII students of SMPIT Ibnu Sina Palopo. This research procedure was carried out in two cycles, with the Kemmis and MC Taggart model which each cycle has four stages, namely: Planning Stage, Implementation Stage, Observation Stage, Reflection Stage. Each cycle consisted of two meetings. The data collection methods used were action observation, field notes, and test sheets. The results of this study are (1) the catch of this study is that the researcher starts the lesson by absent the students, then divides the students into three groups. After that, the researcher distributed questions to the students in the form of questions which were then solved by the scramble method. Then the students presented the results of their work in front of the class (2) The percentage increase in cycle I can be seen that of the 11 students who were complete as many as 6 with a percentage (54.54%), while those who were not complete were 5 people with a percentage (45.46%). As for the second cycle, all students have completed as many as 11 students with a percentage of (100%). From cycle I to cycle II learning outcomes are said to be complete